Kiai’s role as ulama and umara: Implications to the pesantren education - Ahmad Adi Suradi; Buyung Surahman (Masyarakat, Kebudayaan dan Politik, 2020)
This article explains the dualism of the role of kiai pesantren (Islamic boarding school) in Banyuasin Regency, South Sumatera, as ulama and umara, which was later critically elaborated in this research on its implications to the pesantren education. Substantively, this research was inspired by the results of the study of the authors of the 2018 regional elections and ahead of the 2019 elections and presidential elections. The method of this writing can be categorized as qualitative research. The analysis in this paper is carried out on the basis of the concepts of space and field, especially to examine how far the kiai play religious teachings which they believe in social and political behavior in the midst of people’s lives. The results of this study indicate that the rise of kiai who are involved in the world of politics is full of intrigue and conflict among kiai-politicians. One important thing revealed in the involvement of kiai in the political world was that kiai were too close to power, so they used the pesantren for their political interests and made it an instrument for power. For a kiai of pesantren plus politicians, they should be able to carry out their two professions sincerely and istiqomah. If not, the influence of the kiai becomes meaningless, when his authority is deemed to have deviated from what he should have. As a result, many pesantren were abandoned and their development was very alarming. Because of differences in perspective in politics that lead to feuds between the interfaith and the pesantren that they foster.